EpiCO (epirubicin, cyclophosphamide and vincristine) as treatment for extrapulmonary high-grade neuroendocrine neoplasms - Munker, Stefan; Vogelhuber, Martin; Bornschein, Jan; Stroszczynski, Christian; Evert, Matthias; Schlitt, Hans; Herr, Wolfgang; Teufel, Andreas (Zeitschrift für Gastroenterologie, 2020)
High-grade neuroendocrine neoplasms (NEN) comprise a rare entity. Due to the lack of randomized controlled trials, therapy recommendations were mainly extrapolated from its pulmonary analogue, small cell lung cancer and mostly validated in small retrospective case series. The multicentric Nordic NEC Study of gastro-entero-pancreatic (GEP) and cancer of unknown primary (CUP) high-grade neuroendocrine neoplasms showed a significant disease control upon treatment with etoposide and platinum-based chemotherapies 1. Such a combination with etoposide and a platinum (CE) compound is currently considered standard first-line treatment for high-grade GEP/CUP NEN. High-grade mixed-neuroendocrine-non-neuroendocrine neoplasms (MiNEN) formerly termed mixed adeno-neuroendocrine carcinomas (MANEC) also have a poor prognosis and are generally treated like other high-grade NEN. The CE protocol has significant activity in high-grade NEN and MiNEN, but the response is short-lived in most cases with response rates around 50–60 %. Second-line treatment alternatives are not established so far. The need for additional treatment options is evident.Combination chemotherapy with doxorubicin, cyclophosphamide and vincristine (CAV) showed efficacy in small cell lung carcinoma (SCLC) and was considered standard first-line therapy before the era of etoposide and platinum combinations. Due to a better toxicity profile, doxorubicin was replaced by epirubicin, resulting in the combination of epirubicin, cyclophosphamide and vincristine (abbreviated as EpiCO or CEV).In analogy to SCLC, selected patients with high-grade NEN were treated with the EpiCO regimen in second line (or in one patient first line) at our center. In this report we present the retrospective series of 5 cases with metastatic high-grade GEP/CUP NEN/MiNEN who received chemotherapy according to this protocol.
Keywords: neuroendocrine neoplasms; high-grade neuroendocrine carcinoma; mixed-neuroendocrine-non-neuroendocrine neoplasm; mixed adeno-neuroendocrine carcinoma; epirubicin; cyclophosphamide; vincristine